Single nucleotide polymorphisms in candidate genes and their relation with somatic cell scores in Argentinean dairy cattle - Nani, Juan Pablo (2015)
The prevention and control of bovine mastitis by enhancing natural defenses in animals is important to improve the quality of dairy products. Mastitis resistance is a complex trait which depends on genetic components, as well as environmental and physiological factors. The limitations of classical control measures have led to the search for alternative approaches to minimize the use of antibiotics by selecting naturally resistant animals. Polymorphisms in genes associated with the innate immune system are strong candidates to be evaluated as genetic markers. In this work, we evaluated a set of single nucleotide polymorphisms (SNPs) in candidate genes for health and production traits, and determined their association with the somatic cell score (SCS) as an indicator of mastitis in Argentinean dairy cattle. We evaluated 941 cows: Holstein (n = 677) and Holstein × Jersey (n = 264) crossbred, daughters from 22 bulls from 14 dairy farms located in the central dairy area of Argentina. Two of the 21 successfully genotyped markers were found to be significantly associated (p < 0.05) with the SCS: GHR_140 and OPN_8514C-T. The heterozygote genotype for GHR_140 showed a favorable effect in reducing the SCS. On the other hand, heterozygote genotypes for OPN8514C-T caused an increase in the SCS; moreover, combined genotypes for OPN SNPs showed an even larger effect. These findings can contribute to the design of effective marker-assisted selection programs.